MENINGKATKAN KEMAMPUAN GURU DALAM MENERAPKAN MODEL-MODEL PEMBELAJARAN MELALUI KEGIATAN SUPERVISI - Mahin, Mahin (MEDIA DIDAKTIKA, 2022)
The main problem in this research is "Is the application of learning models through classroom supervision activities able to improve the quality of learning for students at SD Negeri 2 Tlanak, Kedungpring District, Lamongan Regency?". Based on the results of this study, it was concluded that the application of learning models through classroom supervision by the school principal proved successful in increasing the ability of SD Negeri 2 Tlanak teachers, Kedungpring District, Lamongan Regency in managing the learning process. In addition, with the increasing ability of SD Negeri 2 Tlanak teachers in Kedungpring District, Lamongan Regency in managing the learning process, not only does the student learning process become more meaningful but also their learning outcomes increase.